The Effect of Problem Based Learning on Fifth-Grade Students’ Speaking Ability in Oral Presentations of Short Stories - Rismayanti, Tuti; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' speaking ability in oral presentations about short stories in grade V of State Elementary School 108 Aekmata, Mandailing Natal Regency, Academic Year 2025–2026. This study used a quantitative approach with a pre-experimental design of one-group pretest-posttest type. The subjects of the study were all 23 fifth grade students, who were selected using a saturated sampling technique. Data were collected through speaking ability tests before and after treatment, and analyzed descriptively and inferentially using the t-test. The results showed that before the implementation of the PBL model, the average pretest score of students' speaking ability was 65.43. At this stage, the majority of students were in the "sufficient" (65%) and "less" (35%) categories, and only 9% achieved learning completion. After the implementation of the PBL model, there was a significant increase with an average posttest score of 84.82. The distribution of scores showed that 48% of students were in the "very good" category, 30% "good", and 22% "sufficient", and 87% of students achieved learning completion. Inferential statistical analysis with the t-test showed that the t-value = 4.016 was greater than t-table = 1.713 at a significance level of 0.05. This means that H₀ is rejected and H₁ is accepted, which shows that there is a significant effect of the implementation of the PBL model on improving students' speaking skills. This improvement is not only seen in academic grades, but also in affective and psychomotor aspects, such as self-confidence, fluency in conveying ideas, and active involvement of students in group discussions. Based on these findings, it is recommended that the Problem Based Learning model be used as an alternative in learning Indonesian to improve students' speaking skills, especially in oral presentations of short stories.